2019
DOI: 10.18178/ijiet.2019.9.11.1310
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement Strategies Vis-à-Vis Academic Performance of Junior High School Students in Mathematics

Abstract: This study covered 237 students of Angat National High School in Taboc, Angat, Bulacan-Philippines particularly the students of Junior High School department for the 2nd Grading Period of the Academic Year 2017-2018. This was delimited to 40 percent sample randomly chosen from the population of 581junior high school, and the 237 parents of the total student respondents. Descriptive correlational method of research was utilized in this study with questionnaire as the main instrument for gathering data. Academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…This shows that there is a positive correlation between parental involvement and student achievement. This shows conformity with previous findings which concluded that parental involvement has a positive effect on achievement at various levels of education, such as kindergarten, elementary, junior high, high school, to adult education and university students (Aquino et al, 2019;Batič & Kac, 2020;Bazán-Ramírez et al, 2022;Cui et al, 2021;Krishnan & A, 2019;Qin et al, 2021;Xiang & Chiu, 2021). This means that the better the involvement of parents, the better the achievement of their children.…”
Section: Discussionsupporting
confidence: 90%
“…This shows that there is a positive correlation between parental involvement and student achievement. This shows conformity with previous findings which concluded that parental involvement has a positive effect on achievement at various levels of education, such as kindergarten, elementary, junior high, high school, to adult education and university students (Aquino et al, 2019;Batič & Kac, 2020;Bazán-Ramírez et al, 2022;Cui et al, 2021;Krishnan & A, 2019;Qin et al, 2021;Xiang & Chiu, 2021). This means that the better the involvement of parents, the better the achievement of their children.…”
Section: Discussionsupporting
confidence: 90%
“…Menurut penelitian, sebagian besar guru PAUD sudah menggunakan gadget sebagai alat bantu dalam kegiatan sehari-hari dan dapat menggunakan fitur-fitur teknologi dengan baik (Aquino et al, 2019;dos Reis et al, 2019;Nasution, 2019;Ng & Teoh, 2019;Waree, 2019). Kelebihan gadget sebagai alat pendukung dalam pembelajaran dan bahan bacaan tidak dapat dipandang sebelah mata (Ishartono et al, 2023;Ishida et al, 2023;Jamaluddin et al, 2023;Richardo et al, 2023;Sagge & Segura, 2023).…”
Section: Pendahuluanunclassified
“…According to Aquino (2013), parental involvement practices in the Philippines are limited and these practices may be different from culture and society to society. Parental involvement may have different types, which might have a differential influence on the academic performance of their children.…”
Section: 2parental Involvement and Academic Performancementioning
confidence: 99%
“…In the local context, the present study which is situated in Dolores District, parental involvement is very limited especially in some school activities which require their participation and collaboration. According to Aquino (2013), parent involvement practices in the Philippines are limited; hence, policies regarding home-collaboration at national, regional, division, and school levels must still be developed. Limited parental involvement in school especially in English learning happened, probably because they do not realize that it is part of parents' duties and obligations to be involved in all aspects of their child's learning.…”
Section: Introductionmentioning
confidence: 99%